2009
DOI: 10.1007/s10552-009-9331-1
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of triple-negative breast cancer, including race

Abstract: Objective Predictors of intrinsic breast cancer subtypes, including the triple-negative (TN) subtype, are largely unknown. We evaluated whether anthropometrics, demographics, and reproductive history were associated with distinct breast cancer subtypes. Methods Invasive breast tumors from a population-based case–control study of 476 (116 black and 360 white) Atlanta women aged 20–54, diagnosed between 1990 and 1992, were centrally reviewed and immunohistochemically analyzed for estrogen receptor (ER), proges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
280
3
14

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(342 citation statements)
references
References 41 publications
35
280
3
14
Order By: Relevance
“…However, there are contradicting findings in the literature regarding the association between TNBC and obesity. Some data specify obesity as a risk factor for TNBC (Millikan et al, 2008;Trivers et al, 2009) while some publications suggest that there is no association between the two (Suzuki et al, 2009;Phipps et al, 2011). The association with obesity is clearly seen in receptor-positive breast cancers, particularly among the postmenopausal group (Vona-Davis and Rose, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are contradicting findings in the literature regarding the association between TNBC and obesity. Some data specify obesity as a risk factor for TNBC (Millikan et al, 2008;Trivers et al, 2009) while some publications suggest that there is no association between the two (Suzuki et al, 2009;Phipps et al, 2011). The association with obesity is clearly seen in receptor-positive breast cancers, particularly among the postmenopausal group (Vona-Davis and Rose, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are based on the current understanding of the heterogeneity of breast cancer development because of hormone and growth factor receptors status. 21 Several studies have demonstrated clear differences in clinical, pathologic, and prognostic characteristics between African-American patients and white patients. 21,[26][27][28] Indeed, gene expression analyses of several breast cancer subtypes have demonstrated differences between African-American patients and non-AfricanAmerican patients, with a higher prevalence of basal-like breast tumors and a lower prevalence of luminal tumors in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Some studies have associated overweight and obesity with the presence of the TN phenotype. 21 To our knowledge, the prevalence and prognosis for Hispanic women with TNBC have not been studied previously. Notably, Mexico has a very high prevalence of overweight and obesity.…”
mentioning
confidence: 99%
“…7 The other recently recognised type of breast cancer are triple-negative tumours, which are characterised by being negative for ER, PR and HER2 and which account for B16% of breast cancers. 7 They have distinguishable epidemiological 8,9 and imaging features. 10 It was initially believed that both Basallike and triple-negative phenotypes were synonymous; however, recent results have suggested that both types may be distinct.…”
mentioning
confidence: 99%